Deconstructing negative pressure wound therapy. Issue 4 (29th September 2016) - Lalezari, Shadi; Lee, Christine J; Borovikova, Anna A; Banyard, Derek A; Paydar, Keyianoosh Z; Wirth, Garrett A; Widgerow, Alan D
Abstract: Since its introduction 20 years ago for the treatment of chronic wounds, negative pressure wound therapy use has expanded to a variety of other wound types. Various mechanisms of action for its efficacy in wound healing have been postulated, but no unifying theory exists. Proposed mechanisms include induction of perfusion changes, microdeformation, macrodeformation, exudate control and decreasing the bacterial load in the wound. We surmise that these different mechanisms have varying levels of dominance in each wound type. Specifically, negative pressure wound therapy is beneficial to acute open wounds because it induces perfusion changes and formation of granulation tissue. Post‐surgical incisional wounds are positively affected by perfusion changes and exudate control. In the context of chronic wounds, negative pressure wound therapy removes harmful and corrosive substances within the wounds to affect healing. When skin grafts and dermal substitutes are used to close a wound, negative pressure wound therapy is effective in promoting granulation tissue formation, controlling exudate and decreasing the bacterial load in the wound. In this review, we elucidate some of the mechanisms behind the positive wound healing effects of negative pressure wound therapy, providing possible explanations for these effects in different wound types.